NanoBiosensing Principles, Development and Application - Ju, Huangxian; Zhang, Xueji; Wang, Joseph; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
This book will cover the full scope of nanobiosensing, which combines the newest research results in the cross-disciplines of chemistry, biology, and materials science with biosensing and bioanalysis to develop novel detection principles, sensing mechanisms, and device engineering methods. It not only covers the important types of nanomaterials for biosensing applications, including carbon nanotubes, carbon nanofiber, quantum dots, fullerenes, fluorescent and biological molecules, etc., but also illustrates a wide range of sensing principles, including electrochemical detection, fluorescence, chemiluminesence, antibody-antigen interactions, and magnetic detection. The book details novel developments in the methodology and devices of biosensing and bioanalysis combined with nanoscience and nanotechnology, as well as their applications in biomedicine and environmental monitoring. Furthermore, the reported works on the application and biofunction of nanoparticles have attracted extensive attention and interest, thus they are of particular interest to readers. The reader will obtain a rich survey of nanobiosensing technology, including the principles and application of biosensing, the design and biofunctionalization of bionanomaterials, as well as the methodology to develop biosensing devices and bioanalytical systems.
Preface -- Biofunctionalization of nanomaterials -- Signal amplification of nanobiosensing -- Nanostructured mimic enzymes for biocatalysis and biosensing -- Porphyrin-based nanocomposites for biosensing -- Carbon nanofiber doped nanocomposites for biosensing -- Biosensing based on nanoporous silica -- Electrochemical biosensing based on carbon nanotubes -- Electrogenerated chemiluminsecence biosensing of quantum dots -- Biosensing application of molecularly imprinted nanoparticles -- Biosensors based on sol-gel nanoparticles matrices -- Nanostructure for nitric oxide electrochemical sensing -- Assembly of nanostructures for taste sensing -- Nanostructured biosensing for detection of insecticides -- Carbohydrate detection using nanostructured biosensing -- Biocompatible nanomaterials for development of immunosensors and immunoassays -- Nanostructured biosensing and biochips for DNA analysis -- Cytosensing and cell surface carbohydrate assay by assembly of nanoparticles -- Nanobiosensing for clinic diagnosis.
Keywords: Engineering; Biomedical engineering; Nanotechnology; Materials Science; Nanotechnology; Biophysics and Biological Physics; Biomedical Engineering; Nanotechnology and Microengineering